2021
DOI: 10.3389/fimmu.2021.667922
|View full text |Cite
|
Sign up to set email alerts
|

c-Rel Is Required for IL-33-Dependent Activation of ILC2s

Abstract: Group 2 innate lymphoid cells (ILC2s) are emerging as important cellular regulators of homeostatic and disease-associated immune processes. The cytokine interleukin-33 (IL-33) promotes ILC2-dependent inflammation and immunity, with IL-33 having been shown to activate NF-κB in a wide variety of cell types. However, it is currently unclear which NF-κB members play an important role in IL-33-dependent ILC2 biology. Here, we identify the NF-κB family member c-Rel as a critical component of the IL-33-dependent acti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…Of note, IL-33 may also promote Th2 differentiation and ILC2 activation via NF-κB activation, which leads to pulmonary fibrosis. 33 , 34 , 35 , 36 , 37 , 38 More research is needed to illustrate the exact role(s) of IL-33 during the recovery stages of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, IL-33 may also promote Th2 differentiation and ILC2 activation via NF-κB activation, which leads to pulmonary fibrosis. 33 , 34 , 35 , 36 , 37 , 38 More research is needed to illustrate the exact role(s) of IL-33 during the recovery stages of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Given the pivotal role of the NF-κB pathway in cytokine production by ILC2, as elucidated in previous studies 4, 45,46 , along with the demonstrated suppressive capability of SHIP-1 on the NF-κB pathway [47][48][49] , our objective was to investigate whether SLAMF3 and SLAMF5 could potentially inhibit the NF-κB signal in ILC2s. We observed a reduction in expression of IκB, an inhibitor of NF-κB whose expression showed an inverse correlation with NF-κB activity 50 , in MLN ILC2s lacking SLAMF3 and SLAMF5 (Fig.…”
Section: Slamf3 and Slamf5 Inhibit Nf-κb Pathway Downstream Il-7/ Il-33mentioning
confidence: 99%